Study on Post Harvest Losses in Potato in Different Storage Conditions - Khanal, Shraddha; Bhattarai, Kabindra (Journal of Food Science and Technology Nepal, 2020)
The study aimed to conduct a comparative study of three most common potato storage conditions (in-house store, in-basket store and cold store) and to find the most suitable storage condition for farmers. The experimental work involved post-harvest loss assessment and study of pattern of respiratory and reducing sugar level for sixty days storage period. Total loss was lowest (4.38%) for cold stored potatoes and highest (13.04%) for in-house stored potatoes. Reducing sugar accumulation was least (0.65%) and remained almost constant throughout study period for in-house stored potatoes. Reducing sugar accumulation gradually increased and was maximum (1.04%) for cold stored potatoes. Respiratory rate was least in cold stored potatoes which gradually decreased and reached 3.17mg CO2/kg/hr at the end of sixty days storage. Respiratory rate was maximum for in-basket stored potatoes which reached up to 6.55 mg CO2/kg/hr at the end of storage. Storage loss and respiratory rate are minimum for cold stored potatoes but showed high sugar accumulation. In-house storage do not suffer from excessive sugar accumulation but storage loss is maximum of all. In case of in-basket storage, besides being cheap and feasible, there is no problem of sugar accumulation and storage losses was also significantly lower than in-house storage.